2020
DOI: 10.1007/s42452-019-1933-y
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and distribution of heavy metals in soil and food crops around the ship breaking area in southern Bangladesh and associated health risk assessment

Abstract: Heavy metal pollution in agricultural soils and food crops around the ship breaking area is of great environmental and human health concern. In this work, we have spectroscopically determined the concentrations of Cd, Pb, Fe, Mn, Zn, Cr, Cu, and Ni in agricultural soils and commonly consumed vegetables, fruits, and rice grain collected from the Sitakunda ship breaking area of Chittagong, Bangladesh, in order to evaluate their contamination levels and probable human health risk with a multivariate statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 40 publications
3
23
1
Order By: Relevance
“…To summarize the pollution level and understand its probable impact on the environment, we have compared all data with the critical maximum concentration, health value, and maximum acceptable value provided by the recognized organizations. Multivariate statistical approaches including Principal Component Analysis (PCA), Cluster Analysis (CA), and Pearson's Correlation Matrix (CM) were also utilized to study the interrelationships among the commonly reported pesticides and the considered South Asian river systems, and thereby to predict the probabilistic origin of the pesticides in the river systems [37,38]. The whole methodology described above is depicted briefly in the form of a flow diagram as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To summarize the pollution level and understand its probable impact on the environment, we have compared all data with the critical maximum concentration, health value, and maximum acceptable value provided by the recognized organizations. Multivariate statistical approaches including Principal Component Analysis (PCA), Cluster Analysis (CA), and Pearson's Correlation Matrix (CM) were also utilized to study the interrelationships among the commonly reported pesticides and the considered South Asian river systems, and thereby to predict the probabilistic origin of the pesticides in the river systems [37,38]. The whole methodology described above is depicted briefly in the form of a flow diagram as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Only those pesticides which are very common in use and reported at a considerable level rather than a very lower level are important to consider for evaluating the effective contamination levels along with their associated probable environmental impact in the studied rivers. For this purpose, the study of the significant associations among the pesticides and the river systems based on their concentration in the samples and also the identification of the probable sources of these chemicals in the rivers are found to be effective and helpful [37,84]. The interrelationships among the reported pesticides and their probabilistic sources in the considered river systems were identified using multivariate statistical analyses such as Principal Component Analysis (PCA), Cluster Analysis (CA), and Pearson's Correlation Matrix (CM) [37,38].…”
Section: Inter Parameters Associations and Probable Sources Of Pesticides In The River Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson's correlation matrices were utilized to identify the associations among the analyzed elements (Tamim et al, 2016;Hasan et al, 2020), and the results are tabulated in Table S4. The strong and significant correlations among the parameters indicate their common sources of origin(s).…”
Section: Source Apportionmentmentioning
confidence: 99%
“…This includes an intensive level of challenging actions, starting with the elimination of all equipment's and device for cutting down and salvaging the structure of the ship. Ship breaking activities are detained accountable for the polluting of the surrounding environments and precious resources like steels along with wood products which are being recuperated for reclaim or recycling reasons [1][2][3][4][5][6][7][8]. Ship breaking may be a demanding procedure, thanks to the structural difficulty of ships and therefore the numerous ecological, safety and health related hazards concerned [9].…”
Section: Introductionmentioning
confidence: 99%